Bens públicos municipais: uso e ocupação na cidade de Fortaleza-CE - Araújo, Henrique Eder Cavalcante (2022)
The analysis of the expansion and dynamics of the urban space of Fortaleza, focusing on the east side, lands of the Antigo Sítio Cocó (ASC), through the planning and disposition of municipal public goods, is the object of this proposed research. The problem of occupation, the contrasts between the environment, the need for infrastructure, legal aspects (subdivisions, management tools, public investments), as well as the use of public goods to consolidate and the advance of urban expansion in Fortaleza reflect the complexity encountered by the different social actors in reconciling the development of the city, as well as the need for expansion proposed for the east side, with the search for environmental, social and urban balance. The legislation applied to urban planning and planning, the construction process of the city of Fortaleza and the use of municipal public assets for the expansion of the municipality, as well as the current typologies, characteristics and destinations of this public heritage in the neighborhoods, in particular the Vicente Pinzón neighborhoods. , Papicu and De Lourdes will be the objective to be achieved in this research. The time frame (1979-2000) is related to the approval of the federal law on federal land subdivision and the municipal land subdivision law, both from 1979, as they represent a legal framework for the consolidation of municipal public assets, until the year 2020 , which is significant for the repercussion of research today. For this, we used the literature focused on the construction of a critical space, which would reflect the socio-spatial dynamics and recognize the holistic process of knowledge in the contradiction of factors. The bibliographic and documentary survey and filing - with the cataloging of laws, documents and reading aimed at understanding theoretically and empirically the aspects of expansion, planning of Fortaleza and the formation of public goods. The visual production - making maps, tables, graphs, charts that facilitate the understanding of urban dynamics and the construction of a database to reflect the object of study - use of geotechnologies (Qgis free software) - were the techniques used greatly in the characterization of the urban space of Fortaleza - east zone - former Cocó site - and to show the municipal public goods constituted in this social and urban dynamics. We identified that the dynamics and urban planning in Fortaleza, from the perspective of both a legal city, that is, that obeyed the urban parameters defined by the legislation, and a city that grew spontaneously, without obeying the rules of subdivision of the land, for example, public goods had a strong influence on the expansion process of the entire city of Fortaleza, especially the east side. We reflect that the study stimulates more debates on the importance ofmunicipal public patrimony in the expansion, consolidation and urban dynamics, as it is an instrument of effective public policies for the city of Fortaleza.